2006
DOI: 10.4319/lo.2006.51.5.2333
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nitrogen limitation on d15N and carbon : nitrogen ratios in sediments from sockeye salmon nursery lakes in British Columbia, Canada

Abstract: Carbon (C) and nitrogen (N) elemental and nitrogen isotopic ratios were determined for bulk organic matter in surface sediments of 11 sockeye salmon (Onchorynchus nerka) nursery lakes in British Columbia, Canada. Chitinous exoskeletons of Bosmina spp. were also picked from the sediments and analyzed for d 15 N. The correlation between salmon escapement (spawner abundance) and bulk organic d 15 N confirms the importance of marine-derived nitrogen to the study lakes. The relation between sediment d 15 N and esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 27 publications
1
31
2
Order By: Relevance
“…As mentioned earlier, we know of no other studies that have examined the long‐term burial of C, N and P, so we cannot evaluate the generality of these trends. Brahney et al. (2006) found that surface sediment C : N ratio varied threefold (from 9–27 molar) among 11 lakes in British Columbia, suggesting that sediment stoichiometry can be quite variable.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, we know of no other studies that have examined the long‐term burial of C, N and P, so we cannot evaluate the generality of these trends. Brahney et al. (2006) found that surface sediment C : N ratio varied threefold (from 9–27 molar) among 11 lakes in British Columbia, suggesting that sediment stoichiometry can be quite variable.…”
Section: Discussionmentioning
confidence: 99%
“…If all available N from the DIN pool is assimilated by algae, the δ 15 N of organic matter would approach that of DIN (Meyers and Lallier‐Verges ; Talbot ; Brahney et al ). The rapid depletion of the DIN pool in all lakes following ice out ( see Whiteford et al ) would tend to suggest that this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…5B and 6). However, under limited nitrogen conditions algae growth may have C/N values as high as 20 (Brahney et al , 2006; Bergström et al , 2008). Thus the somewhat higher C/N corr values of zone 3 are likely a result of low nutrient availability consistent with the diatom record.…”
Section: Interpretation and Discussionmentioning
confidence: 99%